Photographic and descriptive musculoskeletal atlas of orangutans : with notes on the attachments, variations, innervation, function and synonymy and weight of the muscles /: with notes on the attachments, variations, innervation, function and synonymy and weight of the muscles. (2013) - Unknown
No abstract available